The influence of competitiveness on match exercise intensity in elite water polo players - Platanou, T.; Gelades, N. (Biomechanics and Medicine in Swimming X, 2006)
This study was designed to investigate the physiological responses that elicited in different competitive level players during water polo games. Specifically, the hypothesis that the players of International calibre (IA; Greek National Team) perform with higher intensity than the National level players (NA; 1st Greek National League) was tested. Thirty players, who had equally split to IA and NA, participated in this study. No differences were found with respect to the percentage of time spent with exercise intensity above and below the threshold between IA and NA. However, regardless of relative terms (%), IA swam with significantly higher velocity than NA throughout the game. Both groups preferred to compete with an intensity fluctuating around their lactate anaerobic threshold. It is concluded that the International level players performed at higher absolute exercise intensity than National level players.